Rusalki: Anthropology of Time, Death, and Sexuality in Slavic FolkloreRusalky: antropologie času, smrti a sexuality ve slovanském folkloru - Dynda, Jiří (Studia mythologica Slavica, 2017)
<span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">The Eastern Slavic rusalki are feminine mythological beings commonly associated with water, death, and sexuality. They have been thoroughly ethnographically described, classified and compared. This paper presents a re-evaluation of D. K. Zelenin’s classic interpretation of these beings as the souls of women deceased by untimely or unjust death. By means of analysis of their function and embedding in the entire social-cultural environment, it is shown how rusalki make sense in the symbolic system of East Slavic folklore. One of the main goals is to understand how intricately are rusalki and stories about them connected with the Orthodox liturgical year, specifically with the week following Pentecost. The paper concludes that these feminine revenants are symbolic representation of an eternal unripenness, which needed to be annually revived temporarily in order to help the symbolic system to cross the liminal phase of the agricultural and liturgical year cycle.